PENGARUH LIKUIDITAS, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SUB SEKTOR KERAMIK PORSELIN DAN KACA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Br Nainggolan, Jenny Frida; Siahaan, Yansen; Jubi, Jubi; Inrawan, Ady (SULTANIST: Jurnal Manajemen dan Keuangan, 2018)
The purpose of this study is 1. To determine the liquidity, company size, profitability and value of the company in the Ceramic, Porcelain and Glass Sub-Sector Companies listed on the Indonesia Stock Exchange. 2. To determine the effect of liquidity, company size, profitability and firm value on the Ceramic, Porcelain and Glass Sub-Sector Companies listed on the Indonesia Stock Exchange both simultaneously and partially. This research was conducted using quantitative descriptive analysis and quantitative descriptive analysis. The object of the research is the Ceramic, Porcelain and Glass Sub-Sector Company listed on the Indonesia Stock Exchange. Data collection is done by documentation method. The analysis technique used is the classical assumption test, multiple linear regression analysis correlation coefficient, determination coefficient, hypothesis testing. This analysis was carried out using the IBM SPSS Statistic Program version 21.0.The results of this research can be concluded as follows: 1. Overall average value of Current Ratio (CR) fluctuates tends to increase 2. overall the average value of size has fluctuated tends to increase. 3. overall the average value of Return on Assets (ROA) fluctuates but tends to decrease. 4. F test found that simultaneously the magnitude of Fcount> Ftable of H0 is rejected, meaning that liquidity, firm size, and profitability have no significant effect on the value of the company in the Ceramic, Porcelain and Glass Sub-Sector Company listed on the Indonesia Stock Exchange in 2013-2017 .